2002
DOI: 10.1046/j.1440-6047.2002.00296.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different curcumin dosages on human gall bladder

Abstract: Our previous study demonstrated that curcumin, an active compound of Curcuma xanthorrhiza and C. domestica, produces a positive cholekinetic effect. A 20 mg amount of curcumin is capable of contracting the gall bladder by up to 29% within an observation time of 2 h. The aim of the current study was to define the dosage of curcumin capable of producing a 50% contraction of the gall bladder, and to determine if there is a linear relationship between doubling the curcumin dosage and the doubling of gall bladder c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
1
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 12 publications
2
43
1
3
Order By: Relevance
“…Analogous observations were made in another study in which curcumin lowered LDL and increased HDL in atherosclerosis patients [193]. Rasyid et al [194] showed the protective effects of 20 mg of curcumin in improving gallbladder function and reducing gallstone formation. Another trial investigated the effects of curcumin on phosphorylase kinase (PhK) activity in patients with psoriasis [195].…”
Section: Studies Of Curcumin In Human Subjectssupporting
confidence: 67%
“…Analogous observations were made in another study in which curcumin lowered LDL and increased HDL in atherosclerosis patients [193]. Rasyid et al [194] showed the protective effects of 20 mg of curcumin in improving gallbladder function and reducing gallstone formation. Another trial investigated the effects of curcumin on phosphorylase kinase (PhK) activity in patients with psoriasis [195].…”
Section: Studies Of Curcumin In Human Subjectssupporting
confidence: 67%
“…Curcumin is also attractive because of its apparent use and relative pharmacological safety in humans. 34,35 In summary, this investigation demonstrated overexpression of EGFR, p-Akt and p-NF-kB for squamous cell carcinoma of the tonsil and associated high-grade dysplasia, as compared with adjacent non-neoplastic squamous epithelium and tonsillar controls. Overexpressed and translocated p-NF-kB was a marker significantly related to poor prognosis in patients with high-grade dysplasia or squamous cell carcinoma of the tonsil.…”
Section: Discussionmentioning
confidence: 62%
“…Despite the evidence that curcumin is poorly available following oral administration, there are reports that curcumin at 50 -200 mg kg À1 doses exerts biological activity on sites distant from the locus of absorption in rodents, such as breast (Inano and Onoda, 2002), prostate (Frank et al, 2003), lung (Menon et al, 1995) and especially the liver (Busquets et al, 2001;Park et al, 2001;Nanji et al, 2003). Studies on gall bladder contractility following oral curcumin in humans suggest that curcumin may exert biological actions at doses of 20 mg (Rasyid & Lelo 1999;Rasyid et al, 2002).…”
mentioning
confidence: 99%